Land and land tenure in the history of America: an insight into a European heritage to Americans - KPOHOUE, FERDINAND; AHOUANGANSI, S. Raoul (My University, 2016)
The need for new trade routes in the age of discovery opened wide doors to huge interests in land and land cultivation in America, rightly called «the daughter of all Europe » due to certain intrinsic cultural and civilization-based values about Americans. The European land tenure held a high standard place in the making of America as a whole. Set in a constant state of flux, the issue of land was in one way or the other the be-all and the end-all of the early building-up of that land of promise. Drawing on practices linked to the land-holding aristocracy through the feudal age, the sticky stake about the status of persons and the American land-tenure policies, the present paper sets out to look into two centuries of the American life experience. We would then be better prepared to grasp an adequate understanding about the specific importance granted to land in that period of time that impacted the whole nation: a place a great prominence to the land.
Keywords: Land; land tenure; land-holding aristocracy; feudal age; prominence.